Preeclampsia and the risk of large for gestational age infants - Powe, Camille E. (2011)
OBJECTIVE: To compare the risk of giving birth to large for gestational age infants in women with and without preeclampsia, after adjustment for obesity and glucose intolerance. STUDY DESIGN: Prospective cohort study of pregnant women with and without preeclampsia who delivered infants between 1998 and 2006 at Massachusetts General Hospital. RESULTS: The risk of LGA was similar in women with and without preeclampsia (OR 0.81 95% CI 0.59–1.14). After adjustment for body mass index, glucose intolerance, and other factors, the risk of LGA was significantly lower in women with preeclampsia compared to those without preeclampsia (OR 0.69 95% CI 0.49–0.96). Stratified analysis in groups with a higher risk of LGA revealed that preeclampsia has a similar effect on the risk of LGA regardless of maternal obesity, glucose intolerance, parity, and race CONCLUSION: Preeclampsia appears to be characterized by reduced, and not increased, fetal growth.